Dioscin alleviates the progression of osteoarthritis: an in vitro and in vivo study - Qing Ding; Ruizhuo Zhang; Gaohong Sheng; Tianqi Wang; Shaoze Jing; Tian Ma; Shanxi Wang; Hongqi Zhao; Hua Wu; Wenkai Li (BMC, 2023)
Abstract Osteoarthritis (OA) is a common joint disease and is the main cause of physical disability in the elderly. Currently, there is no adequate therapeutic strategy to reverse the progression of OA. Many natural plant extracts have received attention in the treatment of OA due to their potential anti-inflammatory properties, and reduced incidence of adverse events. Dioscin (Dio), a natural steroid saponin, has been demonstrated to inhibit the release of inflammatory cytokines in mouse and rat models of various diseases, and has a protective effect in chronic inflammatory diseases. However, whether Dio alleviates OA progression remains to be explored. In this research, our purposes were to investigate the therapeutic potential of Dio in OA. The results demonstrated that Dio exerted anti-inflammatory effects by repressing NO, PGE2, iNOS and COX-2. Moreover, the application of Dio could repress IL-1β-induced overexpression of matrix metalloproteinases (MMPs, including MMP1, MMP3, and MMP13) and ADAMTS-5, and improve the synthesis of collagen II and aggrecan, which contribute to the maintenance of chondrocyte matrix homeostasis. The underlying mechanism involved the inhibition of the MAPK and NF-κB signaling pathways by Dio. Furthermore, the treatment of Dio significantly improved the pain behaviors of rat OA models. The in vivo study revealed that Dio could ameliorate cartilage erosion and degradation. These results collectively indicate that Dio can be used as a promising and effective agent for the therapy of OA.